Selection of Methods for Microbiological Extraction of Chitin from Shrimp Shells - JUNIANTO JUNIANTO; BUDIASIH WAHYUNTARI; SISWA SETYAHADI (Microbiology Indonesia, 2013)
Chitin extraction from shrimp shells involves two processing steps that are demineralization followed by deproteination process. Lactobacillus acidophilus FNCC 116 and Bacillus licheniformis F11.1 were used in demineralization and deproteination respectively. The overall objectives of this experiment were to determine fermentation systems which resulted in the highest mineral and protein removal. The demineralization experiments consisted of three different batch fermentation designs: batch fermentation (Am ); subsequent batch fermentation 1, in which 100% medium was replaced with fresh medium after 24 h fermentation (Bm ); and subsequent batch fermentation 2, in which 50% medium was replaced with the same amount of fresh medium after 24 h fermentation (Cm ). The demineralization was conducted at 30±2 °C, 50 rpm for 60 h. The deproteination experiments consisted of 3 different batch fermentation designs: batch fermentation 1, inoculum was added once at the beginning of the fermentation (A p); batch fermentation 2, inoculum was added twice, at the beginning and after 24 h fermentation (Bp ); and subsequent batch fermentation, 100% medium was replaced with fresh medium after 24 h fermentation (Cp ). The deproteination was carried out at 55 °C, pH 7.8-8.0, aeration 2.3 vvm, and agitation 275 rpm for 96 h. The experimental results showed that in the demineralization process, fermentation design B gave the highest ash removal. Ash removed in the fermentation design A , B , and C was 97.19, 99.69, and 97.69%, respectively. The protein removed in the fermentation design A , B , and C was 94.42, 94.51, and 95.37%, respectively.